Concerning the Margins Between the Draughts of Ships and the Depths of Fairways - Fagerholm, P. O. (The International Hydrographic Review, 2015)
The fast increase in the draughts of the merchant fleets of the world has caused many problems. This paper deals with the safe distance between ships’ hulls and the sea bottom. It is here especially pointed out that the movements of a ship may cause a considerable momentary increase in its draught. A working group has been organized in Sweden to study this tangle of problems, which are largely correlated. The margin (the difference between the water depth and the draught of a ship at low speed in calm water) when passing a shallow area or a threshold may be divided into two categories, “normal margin” and “ extra margin” . The normal margin calls for exterior conditions, such as sea level, wind pressure, waves, etc., to be "normal". The normal margin is, however, influenced by speed which causes the squat-effect, and which may sometimes be dangerous. Furthermore the normal margin should be based on the assumption that the surveys on the shallowest parts of the fairways are accurately checked, with bar-sweeping for example. When abnormal conditions exist, extra margins should be added to the normal margins. Both the normal margins and the extra margins have been largely based on so-called “ experience”. In so far as such margins have above all an influence on the safety of navigation, this might be acceptable. The fast increase in draughts and the increasingly high construction and dredging costs mean that the margins are of great economic importance. Moreover, the limitation in allowable draught for a harbour has a great influence on shipping and port economy. This paper discusses how "experience" may be substituted by "real knowledge" based on studies, experiments, etc. The various influencing factors are treated one by one. The limited activity of the working group up to November 1964 is reported, as well as its present plans. The paper ends with a recommendation to increase research in this field and to promote international cooperation. The need to keep ships’ officers informed about these problems is stressed.